Focal adhesion-related non-ciliary functions of CEP290 - Kazuhiko Matsuo; Yoshiro Nakajima; Masaki Shigeta; Daisuke Kobayashi; Shinichiro Sakaki; Satoshi Inoue; Naoki Takeshita; Atsuko Ueyama; Kousuke Nishikawa; Rie Saba; Hideya Yamasaki; Kei Yamada; et al. (PLoS ONE, 2025)
Nearly all differentiated mammalian cells possess primary cilia on their surface. Ciliary dysfunction causes ciliopathy in humans. Centrosomal protein 290 (CEP290), a ciliary protein implicated in ciliopathies, localizes to the ciliary base and the centrosome in ciliated cells. CEP290-related ciliopathies arise from molecular dysfunctions of the CEP290 molecule, exhibiting a diverse range of symptoms. Thus far, these disorders have been attributed to cilia-specific functional abnormalities of CEP290, reflecting the conventional view of its primary role within cilia. However, CEP290 is also expressed in proliferating non-ciliated cells and localizes to the centrosome, suggesting potential cilia-independent functions of CEP290 in the pathophysiology of these disorders. In this study, we investigated the cilia-independent functions of CEP290 in non-ciliated cells. Our findings reveal that the loss of Cep290 function impairs microtubule elongation due to malfunction of the microtubule organizing center. Notably, CEP290 forms a complex with adenomatous polyposis coli (APC), a protein that localizes to the centrosome and associates with microtubules. Importantly, reduced focal adhesion formation appears to underlie the phenotypic abnormalities observed in Cep290 knockout cells, including impaired collective cell migration, altered cell morphology, and reduced adhesive capacity to the extracellular matrix. The APC-CEP290 complex plays a consistent and crucial role in stabilizing a focal adhesion molecule, paxillin, at the leading edge in non-ciliated cells. These findings provide a novel framework for understanding the molecular mechanisms underlying ciliopathies, highlighting the importance of CEP290’s cilia-independent functions.